A Mixed Method Content Analysis of Kejhung Madura on Digital Platforms: Cultural Identity through Oral Music Performance - Rully Aprilia Zandra; Kusubakti andajani; Robby Hidajat; Adzrool Idzwan Ismail; Hengki Tri Hidayatullah (Institut Seni Indonesia Yogyakarta, 2025)
This study investigates the representation and preservation of Kejhung Madura, a traditional oral vocal art from Indonesia, within digital media ecosystems. Using a mixed-method content analysis integrating quantitative and qualitative approaches, this research analyzed 119 videos featuring Kejhung Madura across YouTube, TikTok, Facebook, and YouTube Shorts. Quantitative data, such as views, likes, comments, and shares were statistically examined to evaluate audience engagement, while qualitative thematic analysis explored videographic characteristics including duration, lighting, camera movement, and expressive performance. Results show that TikTok generates the highest visibility and engagement, reflecting the adaptability of Kejhung within short-form, algorithm-driven platforms. In contrast, YouTube and Facebook function as digital archives, hosting long-form documentation that maintains cultural integrity. Most videos emphasize individual expression, close-up framing, and natural lighting, indicating a shift from collective performance toward personalized digital reinterpretation. The findings highlight that digital media not only archives but also recontextualizes traditional music into participatory, democratized forms of cultural identity. Therefore, strategic hybridization through creative short clips for engagement and longer formats for preservation can sustain Kejhung Madura’s relevance in the digital era. This study contributes to ethnomusicology and digital heritage studies by demonstrating how oral performance traditions can evolve within global digital culture while retaining their local authenticity.